The Influence of Supervision and Technical Guidelines on Budget Participation and the Effectiveness of Bos Fund Utilization at the Department of Education and Culture of South Kalimantan Province - Anastasia, Maria; Fahri,; Irmapati,; Kadir, Abdul (Archives of Business Research, 2024)
The purpose of this study is to determine and analyze the influence of supervision and technical instructions on budget participation and the effectiveness of the use of BOS funds at the Education and Culture Office of South Kalimantan Province. The method used in this study is a quantitative research method, with the type of explanatory research. The sample used in this study was 60 people, namely the Principal and Treasurer at 30 Schools. Data management in this study will use smartPLS 3.2.7 Software. The conclusion of this study states that Supervision has a positive and significant effect on Budget Participation at the Education and Culture Office of South Kalimantan Province. Technical Instructions have a positive and significant effect on Budget Participation at the Education and Culture Office of South Kalimantan Province. Supervision has a positive and significant effect on the Effectiveness of Fund Use in the Education and Culture Office of South Kalimantan Province. Technical Instructions have a positive and significant effect on the Effectiveness of Fund Use in the Education and Culture Office of South Kalimantan Province. Budget Participation has a positive and significant effect on the Effectiveness of Fund Use in the Education and Culture Office of South Kalimantan Province. Budget Participation mediates the effect of Supervision on the Effectiveness of Fund Use in the Education and Culture Office of South Kalimantan Province. Budget Participation mediates the effect of Technical Instructions on the Effectiveness of Fund Use in the Education and Culture Office of South Kalimantan Province.